Perlindungan Konsumen terhadap Tindakan Wanprestasi Produk E-Commerce - Febriansyah, Muhammad Vico; Mbaling, Constantius Mario Valentino; Tapilatu, Finsri Metanoya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In e-commerce, there are often cases where customers are not satisfied with COD (Cash on Delivery) packages. Problems that often occur include delivery delays, lost packages, discrepancies between orders and products received, and difficulty canceling orders if there are problems or errors in delivery. Customers who experience COD delivery problems may lose trust in the seller and the e-commerce platform. Therefore, sellers and e-commerce platforms should ensure timely delivery of cash-on-delivery parcels in line with customer expectations, and resolve issues quickly and efficiently when they arise. By doing so, customer trust can be maintained and COD services can be used in the future. Keywords: e-commerce; selling shop